The Role of Banking Services in Determining the Destination Countries for Indonesia’s Non-Oil and Gas Export - Rini Satriani; T. M. Zakir Machmud (Institute for Economic and Social Research, 2020)
This study aims to examine whether the risk factor and banking services play a significant role in determining not only the export performance of a country but also the pattern of export destination markets, with the reference to the case of Indonesia. These two indicators are interrelated because the risk factor in export transactions can be mitigated by banking sector. Using the data of export Letter of Credits (LCs) for non-oil and gas exports of Indonesia as a banking instrument to mitigate special risk transactions to 102 export destination countries as well as a panel data methodology for the 2011–2018 period, this study discovers that the risk of export destination countries affects the decline in non-oil and gas exports of Indonesia to the alleged high-risk countries that are non-traditional export markets of Indonesia by 8.34%. In contrast, the LCs only significantly affect the increase in non-oil and gas exports of Indonesia to the lowand medium-risk countries by 0.024–0.029%, most of which are traditional export markets of Indonesia. It implies that banking sector in general does not have the appetite for providing financing for Indonesian exporters attempting to penetrate non-traditional export markets. This result underlines that commercial banks in Indonesia have a significant role in shaping the pattern of destination countries for Indonesian export. Consequently, government intervention is essentially needed by assuming or sharing part of the risk with state banks supposing the government continues to expect exporters to be able to penetrate into the non-traditional countries.